Health Education On Balanced Nutrition in Toddlers in Teluk Pinang Village - Nina Yusnia; Citra Resmi Lestariana Putri (AbdimasMu UMTAS, 2022)
Introduction: Knowledge of balanced nutrition in toddlers in Indonesia is still relatively low. Of the 37.2% of toddlers in Indonesia, only 13.0% experienced malnutrition status based on age and 2.5% who experienced thinness based on weight compared to height. This means that there are only 13.0% and 2.5% of children under five who have been malnourished from a long time until now, low balanced nutrition knowledge has resulted in Indonesia still facing nutritional problems in toddlers such as malnutrition. Purpose: To determine the effect of "balanced nutrition" education on maternal knowledge in fulfilling "balanced nutrition" in toddlers in Teluk Pinang Village. Method: The method carried out is the lecture method, in this community service, the speaker team provides understanding to 22 mothers who have toddlers. Results: The results of statistical test calculations obtained a t value of 6,953 and p = 0.000 (p<001), meaning that there is an influence of balanced nutrition education for toddlers. From the results obtained from the pre-test and post-test, it shows an increase in participants' understanding from an average pre-test value of 60 to an average post test value of 75. Conclusion: This "balanced nutrition" education can be influenced on mothers who have toddlers, especially for mothers who are poorly educated and relatively young to be able to increase knowledge in meeting the nutrition of toddlers in Teluk Pinang Village.